AB1155-HPR The Relationship of Goal Management with Fatigue over One Year in Patients with Polyarthritis. (10th June 2014) - Bode, C.; Taal, E.; Arends, R.Y.; Van de Laar, M.
Abstract : Background: Many patients with polyarthritis experience severe fatigue. How to cope with severe fatigue in polyarthritis is unclear. For related symptoms as pain, depressive feelings and feelings of anxiety some studies have pointed to the beneficial effects of goal management. Objectives: Aim of this study was to describe the relationship of four goal management strategies (goal maintenance, goal adjustment, goal disengagement, goal re-engagement) and fatigue (severity, impact and coping) in a longitudinal perspective. Methods: 331 patients (61% women, mean age=61 years, mean disease duration=14 years) participated in a questionnaire study with measurements at baseline, after six and twelve months. Goal management was measured by TenFlex and GAS, fatigue was assessed by 3 visual analogue scales, asking for the severity and impact of fatigue and coping with fatigue. Results: The studied aspects of fatigue and the use of goal management strategies were stable over the course of one year. In regression analyses higher use of goal adjustment was significantly related to less severe fatigue, less impact of fatigue and better coping with fatigue. Unexpectedly, higher goal reengagement was related to more severe fatigue. Goal maintenance and goal disengagement did not contribute to the explanation of fatigue. Conclusions: The results indicated stability of goal management and levels of fatigue over one year. For patients with elevated levels of fatigue it might be beneficial to change the way they deal with fatigue by adjusting personal goals. The role of goal re-engagement in relation to fatigue should be further explored since previous studies with related symptoms showed opposite relationships. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4657